Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/su15097608
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Behavior According to the Development of Sustainable Pistachio (Pistacia vera L.) Rice Cake: For Korean Consumers

Abstract: In recent years, the rice cake market has grown considerably in terms of research and development of products suitable for consumer needs and beneficial to health at the same time. Since the outbreak of COVID-19, the number of consumers consuming antioxidant-rich foods and immunity-boosting foods to improve health and promote healthy eating habits has increased. Pistachio rice cakes have been tested and found to be high in polyphenols, which have good antioxidant activity and strengthen the immune system. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…However, the actual cause of this problem may not be resolved; therefore, countermeasures are needed. Accordingly, this change in consumer awareness emphasizes safer edible products and sustainable safety that are mindful of the environment and the earth [12,59]. One study assessing the public knowledge and potential health impacts of global warming in Ghana surveyed Ghanaian adults (N = 1130) from 1 November 2018, to 28 February 2019, and found a consistent result that approximately 84.4% of the respondents understood the meaning of global warming.…”
Section: Changes In Consumer Needs Due To Accelerating Global Warmingmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the actual cause of this problem may not be resolved; therefore, countermeasures are needed. Accordingly, this change in consumer awareness emphasizes safer edible products and sustainable safety that are mindful of the environment and the earth [12,59]. One study assessing the public knowledge and potential health impacts of global warming in Ghana surveyed Ghanaian adults (N = 1130) from 1 November 2018, to 28 February 2019, and found a consistent result that approximately 84.4% of the respondents understood the meaning of global warming.…”
Section: Changes In Consumer Needs Due To Accelerating Global Warmingmentioning
confidence: 99%
“…These events have been associated with acute exacerbation of skin injuries, skin infections, and inflammatory skin diseases [4]. In addition, since the outbreak of COVID-19, various studies have been conducted on skin health to promote health, healthy eating habits, and sustainable safety [10][11][12]. Some studies on the topics of global warming and consumer desire for safe ingredients are shown in Table 1.…”
Section: Changes In Consumer Needs Due To Accelerating Global Warmingmentioning
confidence: 99%
See 3 more Smart Citations